Modeling web services choreography dancing with BPMN and new eclipse tool pi4soa. - Havey, Michael
Choreography is the dark continent of web services : few onlookers have traveled there and many question whether there are any riches to be brought home from the trip. In the first place, choreographies bear such a striking resemblance to business processes that the novice might think that the two types of artifacts are indistinguishable.